Addressing challenges of principal turnover strategies of teachers and principals - Miguel, Angeline C. (College of Education, University of the Philippines Diliman, 2019)
The purpose of this study was to identify the reasons of principal turnover, how the turnover affected the principals and teachers by identifying the challenges they encountered, and how they cope with these challenges. Five schools from the City of Mandaluyong were selected to participate in the study. Each school had three to six changes of principals for the past five School Years, from 2014-2015 to 2018-2019. Interviews were done to five principals and nine teachers for data collection. Based on the results of the cross-case analyses of five schools, there were eleven reasons why principals changed post, while five themes emerged on the challenges faced by the principal and eight themes on their turnover strategies. Regarding the cross-case analysis of the teachers responses, four themes came up on the challenges they encountered during the turnover and three themes were identified on their coping strategies. Principals turnover is inevitable, as well as the challenges that come with it. Therefore, the results in this study provide insights to schools leaders and policymakers in addressing the issues of principals turnover by overcoming the challenges through the effective turnover strategies of principals and coping strategies of teachers presented.